Companions in Guilt Arguments and Moore’s Paradox - Campbell, Michael Walter (My University, 2017)
In a series of articles Christopher Cowie has provided what he calls a ‘Master Argument’ against the Companions in Guilt (CG) defence of moral objectivity. In what follows I defend the CG strategy against Cowie. I show, firstly, that epistemic judgements are relevantly similar to moral judgements, and secondly, that it is not possible coherently to deny the existence of irreducible and categorically normative epistemic reasons. My argument for the second of these claims exploits an analogy between the thesis that epistemic norms are non-categorical and G.E. Moore’s paradox concerning first personal belief ascriptions. I argue that the absurdity of the assertion “I have evidence that p but no reason to believe it” shows that the norms of belief are categorical. I then consider the counter-argument that this categoricity is a ‘conceptual’ rather than an ‘objective’ requirement. By drawing on the work of Hilary Putnam and Charles Travis, I show that this counter-argument is unsuccessful. Putnam is one of the original proponents of the Companions in Guilt strategy. Thus, by supporting the CG argument through appeal to other Putnamian theses, I show that its insights can only fully be appreciated in the context of broader metaphysical and semantic lessons.
Companions in Guilt Arguments and Moore’s Paradox
Keywords: companions in Guilt; epistemic reasons; error theory; meta-ethics; moral objectivity; normativity; companions in Guilt; epistemic reasons; error theory; meta-ethics; moral objectivity; normativity